Macroparasite communities of wild rats from island and coastal habitats in Peninsular Malaysia / Nur Syazana Binti Mad Tahir - Mad Tahir, Nur Syazana (2013)

(untitled)
The occurrences of macroparasites communities in 363 wild rats of two urban coastal cities (Kuantan and Malacca) and two islands (Carey Island and Penang) of Peninsular Malaysia were recorded between May 2010 to August 2011. The wild rats from both habitats comprised of mainly commensal rat species namely; Rattus norvegicus, Rattus rattus diardii, Rattus tiomanicus and Rattus argentiventer. Overall, higher numbers of females (60.3%) were captured compared to males (39.7%) with more adults (87.9%) compared to juveniles (12.1%). The rats were infected with a minimum of one species and a maximum of six species of ectoparasites while up to five species of endoparasites were seen in each rat. In R. norvegicus the highest number of ecto and endoparasites infestation/infection was seen respectively. There were no differences in the types of macroparasites recovered from both coastal and island rat populations. Overall, ectoparasites diversity index was low for all sites, although Carey Island recorded higher index compared to other locations with 8 numbers of species. Nine cosmopolitan ectoparasite species were recovered in total with 5 mite species, (Laelaps nuttali, Laelaps echidninus, Ornithonyssus bacoti, Listrophoroides sp., Laelaps sculpturatus) 2 lice, (Polyplax spinulosa, Hoplopleura pacifica,) one flea (Xenopsylla cheopis) and one tick (Ixodes granulatus). Host sex (male and female) and host age (adult and juvenile) did not influence ectoparasite infestation on the rat population. However, seasons played a significant role with Ornithonyssus bacoti, Laelaps sculpturatus, Polyplax spinulosa, Hoplopleura pacifica and Ixodes granulatus with higher infestion during wet compared to dry season. Endoparasites infections comprised entirely of cosmopolitan species, namely Nippostrongylus brasiliensis, Angiostrongylus malaysiensis, Capillaria hepatica, Mastophorus muris, Heterakis spumosa, Hepatojarakus malayae, Syphacia muris, iii Taenia taeniaeformis, Hymenolepis diminuta and Rodentolepis (=Hymenolepis) nana. Species diversity index was low in all locations. Host sex influenced endoparasitic infection only for Capillaria hepatica, Syphacia muris and Rodentolepis (=Hymenolepis) nana while other helminths (Hepatojarakus malayae, Taenia taeniaformis, Rodentolepis (=Hymenolepis) nana) showed significant effects between host ages. Season also played a significant role determining diversity and prevalence for most endoparasite species with higher infection observed during the dry season. Despite low diversity, seven ectoparasites (Laelaps nuttali, Laelaps echidninus, Ornithonyssus bacoti, Polyplax spinulosa, Hoplopleura pacifica, Ixodes granulatus and Xenopsylla cheopis) and 5 helminths species (Capillaria hepatica, Angiostrongylus malaysiensis, Hymenolepis diminuta, Taenia taeniaeformis, Rodentolepis (=Hymenolepis) nana) recovered were zoonotic. The close association between the rat populations with human may facilitate the transmission of zoonotic parasites circulating in these ecosystems. Therefore, long term monitoring of the rodent population is necessary in order to predict future disease prevalence.